2020
DOI: 10.1017/ice.2020.362
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on pneumonia-focused antibiotic use at an academic medical center

Abstract: To the Editor-Optimizing antimicrobial use and stewardship during the global spread of severe acute respiratory coronavirus virus 2 (SARS-CoV-2) is an important goal for health systems. A review published in May 2020 found that only 8% of patients with coronavirus disease 2019 (COVID-19) had a bacterial or fungal coinfection, while 72% of patients received antimicrobial therapy. 1 Many patients requiring hospitalization for COVID-19 present with symptoms mimicking community-acquired bacterial pneumonia prompti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 4 publications
(4 reference statements)
6
39
0
1
Order By: Relevance
“…The marked increase in the use of azithromycin and ceftriaxone in the early weeks of the COVID-19 epidemic in Italy is similar to that observed by Nestler et al at an 865-bed urban academic medical centre in Virginia, USA, in April 2020 when the epidemic exploded there [ 4 ]. A large study carried out at 84 facilities of the Veterans’ Health Administration in the USA also found a significant increase in antibiotic consumption during the period January–May 2020, with the largest increase being observed in the case of the antibiotics used to treat CAP and broad-spectrum antibiotics in general [ 5 ].…”
supporting
confidence: 70%
See 1 more Smart Citation
“…The marked increase in the use of azithromycin and ceftriaxone in the early weeks of the COVID-19 epidemic in Italy is similar to that observed by Nestler et al at an 865-bed urban academic medical centre in Virginia, USA, in April 2020 when the epidemic exploded there [ 4 ]. A large study carried out at 84 facilities of the Veterans’ Health Administration in the USA also found a significant increase in antibiotic consumption during the period January–May 2020, with the largest increase being observed in the case of the antibiotics used to treat CAP and broad-spectrum antibiotics in general [ 5 ].…”
supporting
confidence: 70%
“…It is interesting to note that, like Nestler et al [ 4 ], we observed a rapid reversal of azithromycin and ceftriaxone consumption to pre-epidemic values and, albeit in the absence of published reports and clear guidelines, it can be speculated that increasing knowledge of COVID-19 led us to reconsider the empirical use of antibiotics to treat CAP [ 3 ]. In our opinion, the main opportunity for reducing inappropriate antibiotic consumption is at the time of hospital admission, when a pre-hospital prescription of empiric antibiotic treatment can be censored or a new prescription avoided in the absence of clear signs of superimposed infection.…”
mentioning
confidence: 60%
“…A single-center study at an academic hospital in Virginia reported significantly increase use of ceftriaxone and azithromycin but not of other broad-spectrum antibiotics coincident with the onset of the pandemic. 1 Another single-center study from Spain showed increased use of amoxicillin-clavulanate during the early phase of the pandemic, followed by later increased utilization of broad-spectrum antibiotics. 2 There are several potential explanations for the observed increases in antimicrobial use including concerns of bacterial co-infection in suspected or newly diagnosed COVID-19 patients, increased risk of nosocomial infection due to administration of immunomodulatory therapy, reluctance to obtain diagnostic respiratory specimens, 3 diversion of clinical resources from stewardship activities during a time of crisis, and an increased proportion of hospitalizations being due to respiratory infections which typically prompt antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of increased antibiotic use during the COVID-19 pandemic have generally been from heavily impacted facilities or geographic regions and provide few details regarding patterns of antibiotic use. [1][2][3] To provide a broader overview of changes in antibiotic use in a healthcare system with a long-standing enterprise-wide commitment to antibiotic stewardship, we compared patterns of antibiotic use throughout the VA from January-May 2020 with corresponding time periods in prior years.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, surges in COVID-19 cases have led to antibiotic overprescribing in the inpatient setting, hampering ongoing antimicrobial stewardship efforts. 1,2 However, patients' reluctance to seek healthcare during the pandemic, particularly for minor ailments, may lead to unexpected outpatient antimicrobial stewardship gains. Jeffery et al 3 reported an inverse relationship between COVID-19 cases and daily counts of emergency department visits in 5 US states between January and April of 2020.…”
mentioning
confidence: 99%